Overturning the "bowle of creame": some reflections on intertextuality and gender - Martínez Alfaro, M.ª Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
Many are the factors which should be taken into account when it comes to analyzing what has increasingly become one of the defining features of contemporary literature, both in its modernist and postmodernist phases. In this article, I intend to show the influence that questions of gender have had upon the complex phenomenon of intertextuality. Feminist criticism has contributed to widening the intertextual field by bringing to the fore the neglected work of female authors. Moreover, traditional works by male writers have been re-read and re-interpreted, while well-known literary conventions have become subverted in an attempt to present experience from an-other point of view. To illustrate this fact, I have compared two sets of poems which approach, from different perspectives, the subject of the female body. The intertextual house has many rooms and many voices, and each newcomer demands from us to see the whole in a new, ever changing light.
Keywords: Intertextuality; gender